CONSTRAINTS ON THE DEVELOPMENT OF CLOUD COMPUTING SERVICES - D. S. Serzhanova (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the main types of cloud computing services and their descriptions. Presents the main factors of cloud computing in modern areas of advanced information technology and some advantages for users as well as the supporting factors for the development of Cloud Computing services.